2009
DOI: 10.2217/nnm.09.28
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Antibacterial Activity of Doxycycline-Loaded Poly( D , L -Lactide-Co-Glycolide) and Poly(ε-Caprolactone) Nanoparticles

Abstract: The mean particle size ranged from 230 to 360 nm, as measured by dynamic laser light scattering, and scanning-electron microscopy confirmed the spherical nature and smooth surface of the nanoparticles. Fourier transform infrared spectroscopy analysis of void nanoparticles, drug-loaded nanoparticles and native DXY indicated no interaction between the drug and polymer in the nanoparticle. Differential scanning calorimetry analysis of drug-loaded nanoparticles indicated a molecular level dispersion of DXY in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 40 publications
3
71
0
Order By: Relevance
“…Moreover, the MIC and MBC of NFX-SLN were the same as that of native NFX at 12 h, and lower than that of native NFX at 24 h, suggesting that SLN increased the antibacterial activity of NFX. These results are similar to those obtained by Ranjita Misra et al and Esmaeili et al (Misra et al, 2009;Esmaeili et al, 2007). Fusion of the lipid composition with the bacterial membranes might account for the enhanced antibacterial effect of NFX-SLN (Sachetelli et al, 2000).…”
Section: Antibacterial Activitysupporting
confidence: 90%
“…Moreover, the MIC and MBC of NFX-SLN were the same as that of native NFX at 12 h, and lower than that of native NFX at 24 h, suggesting that SLN increased the antibacterial activity of NFX. These results are similar to those obtained by Ranjita Misra et al and Esmaeili et al (Misra et al, 2009;Esmaeili et al, 2007). Fusion of the lipid composition with the bacterial membranes might account for the enhanced antibacterial effect of NFX-SLN (Sachetelli et al, 2000).…”
Section: Antibacterial Activitysupporting
confidence: 90%
“…36 In this study the zeta potential of a nanoparticle was −20.7 ± 1.2 mV, which was high enough to make the nanoparticles repel each other, thereby avoiding particle aggregation and keeping the long-term stability of nanoparticles. 37,38 Second, X-ray diffraction was used to investigate the nature of curcumin after encapsulation into the SLNs. It was observed that curcumin entrapped in the lipid core of the SLN was in the amorphous or disordered-crystalline phase.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Previous studies throughout the literature have applied lipid-based approaches (liposomes, solid lipid nanoparticles, nanoemulsions, and microemulsions) and polymerbased nanocarriers (nanocapsules and nanospheres) to enhance the antimicrobial activity of antibiotics (including β-lactams). [34][35][36][37][38][39] Nanoantimicrobial agent synthesis studies have recently increased in number; however, most of these agents are nonantibiotic-based nanoparticles, primarily metal-based nanoparticles that use silver, copper, and zinc, among other metals. This study aimed to prepare the first amp-chitosan-iron oxide nanocomposite for numerous applications such as a novel nanoantibiotic pharmaceutical agent to combat various bacterial diseases.…”
Section: Introductionmentioning
confidence: 99%